Is there a text in this cave? : studies in the textuality of the Dead Sea Scrolls in honour of George J. Brooke - Brooke, George J.; Feldman, Ariel, 1974- (Studies on the Texts of the Desert of Judah, 2017)
This volume is offered as a tribute to George Brooke to mark his sixty-fifth birthday. It has been conceived as a coherent contribution to the question of textuality in the Dead Sea Scrolls explored from a wide range of perspectives. These include material aspects of the texts, performance, reception, classification, scribal culture, composition, reworking, form and genre, and the issue of the extent to which any of the texts relate (to) social realities in the Second Temple period. Almost every contribution engages with Brooke's own remarkably wide-ranging, incisive, and innovative research on the Scrolls. The twenty-eight contributors are colleagues and students of the honouree and include leading scholars alongside promising new voices from across the field.